Design Ethnic-Math HOTS: Mathematics Higher Order Thinking Skill Questions Based On Culture and Local Wisdom - Mulyatna, Fauzi; Imswatama, Aritsya; Rahmawati, Novia Dwi (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The design of HOTS Ethnic-Mathematics is the stage that has been intended in this study. This type of research is research and development (Research and Development) by producing results in the form of Mathematics Higher Order Thinking Skill (HOTS) questions based on culture and local wisdom (Ethnic-Math HOTS). The development model referred to by the researcher is the Analysis, Design, Development, Implementation and Evaluation (ADDIE) which is adapted into Analysis, Design, and Development (ADD). The conclusion of this paper is Mathematical problem designs that are integrated with local culture and local wisdom can be developed into questions that have a function to measure students' high-level abilities. High-level abilities that can be measured using these questions are analytical skills, evaluation skills and creative abilities. By completing questions related to the culture in the area around students, students will be more challenged and motivated to do it. In addition, it will increase students' knowledge about the local culture in the area.